Diffusion and Perfusion MRI Predicts Response Preceding and Shortly After Radiosurgery to Brain Metastases: A Pilot Study. Issue 2 (28th December 2020) - Shah, Akash Deelip; Shridhar Konar, Amaresha; Paudyal, Ramesh; Oh, Jung Hun; LoCastro, Eve; Nuñez, David Aramburu; Swinburne, Nathaniel; Vachha, Behroze; Ulaner, Gary A.; Young, Robert J.; Holodny, Andrei I.; Beal, Kathryn; et al.
ABSTRACT: BACKGROUND AND PURPOSE: To determine the ability of diffusion‐weighted imaging (DWI) and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) to predict long‐term response of brain metastases prior to and within 72 hours of stereotactic radiosurgery (SRS). METHODS: In this prospective pilot study, multiple b ‐value DWI and T1‐weighted DCE‐MRI were performed in patients with brain metastases before and within 72 hours following SRS. Diffusion‐weighted images were analyzed using the monoexponential and intravoxel incoherent motion (IVIM) models. DCE‐MRI data were analyzed using the extended Tofts pharmacokinetic model. The parameters obtained with these methods were correlated with brain metastasis outcomes according to modified Response Assessment in Neuro‐Oncology Brain Metastases criteria. RESULTS: We included 25 lesions from 16 patients; 16 patients underwent pre‐SRS MRI and 12 of 16 patients underwent both pre‐ and early (within 72 hours) post‐SRS MRI. The perfusion fraction ( f ) derived from IVIM early post‐SRS was higher in lesions demonstrating progressive disease than in lesions demonstrating stable disease, partial response, or complete response ( q = .041). Pre‐SRS extracellular extravascular volume fraction, v e, and volume transfer coefficient, K trans, derived from DCE‐MRI were higher in nonresponders versus responders ( q = .041). CONCLUSIONS: Quantitative DWI and DCE‐MRI are feasible imaging methods in the pre‐ and early (within 72 hours) post‐SRS evaluation of brain metastases. DWI‐ and DCE‐MRI‐derived parameters demonstrated physiologic changes (tumor cellularity and vascularity) and offer potentially useful biomarkers that can predict treatment response. This allows for initiation of alternate therapies within an effective time window that may help prevent disease progression.